Diagnostic Imaging and Biopsy Use Among Elderly Medicare Beneficiaries With Hepatocellular Carcinoma - Massarweh, Nader N. (American Society of Clinical Oncology, 2011)
PURPOSE: Diagnostic imaging is effective for evaluating patients suspected of having hepatocellular carcinoma (HCC). Although the diagnosis can be established with imaging alone, diagnostic biopsy may be useful for patients with tumors measuring 1 to 2 cm. To date, biopsy and imaging use among patients with HCC has not been evaluated in the general community. PATIENTS AND METHODS: This cohort study used Surveillance, Epidemiology, and End Results (SEER) -Medicare data (2002-2005) evaluating biopsy, imaging modalities (ultrasound, computed tomography [CT] scan, and/or magnetic resonance imaging [MRI]), and HCC risk factors. RESULTS: Of 3,696 patients, 1,197 (32.4%) underwent one or more biopsies, with no change in yearly biopsy rate (trend test, P = .64). Patients with tumors > 5 cm were most likely to receive biopsies (35.3%), with increasing rates of biopsy for larger tumors (P = .001). Patients who received biopsies underwent more imaging than those who did not (P < .001) and were more likely to have an HCC risk factor. Tumor size > 5 cm in the setting of a concurrent HCC risk factor increased the odds of biopsy. In 47.8% of patients, the diagnostic sequence was not consistent with contemporary evidence-based guidelines. CONCLUSIONS: Despite widespread availability and use of CT scan and MRI, one third of HCC patients undergo biopsy, suggesting a problem with the performance and/or quality of diagnostic imaging or that providers do not believe imaging alone is sufficient to establish the diagnosis. Understanding factors that drive biopsy use may help improve the care of patients with HCC.